Characterization of Seaweed Caragenan Eucheuma cottonii and Its Aplication as Edible coating - Supriwanti, Supriwanti; Warsidah, Warsidah; Prayitno, Dwi Imam (Universitas Jember, 2023)
Seaweed E. cottonii is carragaenophytes or carrageenan-producing plant. Carrageenan has a functions stabilizer, thickener and gel former, so it can be used as edible coating that can maintain fish quality. Tuna has nutritional content per 100 grams such protein around 25-26.2%; water 69.40%; fat 1.50%; and carbohydrates 0.03%. Tuna filets quickly decompose if proper handling is not carried out, it is necessary to apply edible coating because this edible coating can protect the product from air contamination and can prevent microbial growth. This study aims to determine the effect of extraction time characteristics of carrageenan and the appropriate concentration of carrageenan for edilbe coating tuna filet. The extraction process was carried out by heating dried seaweed samples with 8% KOH solution for 1 hour, 2 hours and 3 hours at a temperature of 50˚C. The best characteristics of carrageenan resulted from 2 hours of extraction time with 40% yield, 14.95% water content, 63 dPas viscosity and 12.396 ppm sulfate content. The best carrageenan was applied as edible coating on tuna filets with 3 concentrations, namely 1.5%, 2% and 2.5%, each of which was added with 2 mL of glycerol. Based on the Total Plate Count (TPC), it was found that a carrageenan concentration of 2.5% could prevent bacterial growth in the sample as indicated by the TPC number obtained at 2.7×106, which was lower than the control, which was 1.7×107.